The Revolution of Brix 3000 as Chemomechanical Caries Removal (Cmcr) Agent, A Scoping Review - Dewi, Aninda Kartika; Gartika, Meirina (Dentistry Faculty, 2024)
Background: Traditional caries removal techniques, like using a vibrating drill, have several drawbacks, including unpleasant sensations, heat that can irritate dental pulp, the need for local anesthesia, high energy consumption, and environmental concerns. A new method, CMCR (chemomechanical caries removal) with Brix 3000, aims to address these issues. It is minimally invasive, painless, and comfortable, promoting a positive attitude towards dental care, especially for pediatric patients, those with anxiety or fear, and high-risk medical patients. Objective: This literature review examines the use of Brix 3000 gel for chemomechanical caries removal. Methods: The study uses a scoping review method, conducting a comprehensive literature search on PubMed, EBSCO, ScienceDirect, Scopus, ClinicalTrials.gov, and Google Scholar databases. The search focused on articles from the last 10 years using keywords like